Tepache Kulit Nanas - Erie Hidayat Sukriadi; Wahyu Teresza Rustomo; Rachmat Astiana (Jurnal Pariwisata Indonesia, 2022)
This study aims to utilize waste so that it can be utilized and become a selling point by conducting experiments on the waste, the waste used in this research is pineapple peel which will be tested into tepache. Tepache is a traditional drink from Mexico. In this study, experiments with organoleptic tests were carried out with three experimental formulations, namely X1, X2 and X3. Data collection techniques using observation, interviews and literature study. From the three formulations, the X3 experiment was declared successful and the experiment was continued into a drink mixture. The drinks he tested were Sensation and Virgin Pinacolada, after adding tepache X3 only Virgin Pinacolada was suitable and enjoyed. So that this research can contribute to beverage sellers to be used as one of the types of menus they sell.